Child abuse via the internet In the United Arab Emirates and how to protect them: (Empirical Study) - Al-Musafri, Aisha Saeed; Alomosh, Ahmad Falah (Al-Adab Journal, 2020)
This study aims to identify the reasons that children are exposed to abuse via the internet and the most important negative aspects of using the Internet from the viewpoint of the families whose children use the internet networks in the UAE society, and for the purposes of that, special questionnaires were designed for the subject of the study, the first was applied to (420) and the sample included (210) Male and female students, of whom (105) are male and 105 female, and the second included a sample of (210) from families whose children use the Internet in the Emirates. The results of the study revealed that the contributing causes of child abuse via the internet were the result of children forming friendships and relationships without family science and using the Internet repeatedly and late times without family science. As for the results of the study on the negative aspects of using the Internet from the viewpoint of families whose children use the Internet in the UAE society, they were as follows: the negative impact on Internet users and the reluctance to study and contribute to the promotion of pornography and the promotion of Western culture. The results of the study revealed the reasons that children are exposed to abuse, which were the lack of interest in media programs and community institutions to educate children about the safe use of the Internet. The study concluded with several recommendations, the most important of which is to emphasize the role of society and the family in facing the seriousness of child abuse via the internet, and stressed the importance of the educational role of the educational institution in educating children about safe ways to use the Internet, benefit from its positives and avoid its risks.